# Solve for t -3(t-5)+7t=6t-8 -3(t-5)+7t=6t-8
Simplify -3(t-5)+7t.
Simplify each term.
Apply the distributive property.
-3t-3⋅-5+7t=6t-8
Multiply -3 by -5.
-3t+15+7t=6t-8
-3t+15+7t=6t-8
Add -3t and 7t.
4t+15=6t-8
4t+15=6t-8
Move all terms containing t to the left side of the equation.
Subtract 6t from both sides of the equation.
4t+15-6t=-8
Subtract 6t from 4t.
-2t+15=-8
-2t+15=-8
Move all terms not containing t to the right side of the equation.
Subtract 15 from both sides of the equation.
-2t=-8-15
Subtract 15 from -8.
-2t=-23
-2t=-23
Divide each term by -2 and simplify.
Divide each term in -2t=-23 by -2.
-2t-2=-23-2
Cancel the common factor of -2.
Cancel the common factor.
-2t-2=-23-2
Divide t by 1.
t=-23-2
t=-23-2
Dividing two negative values results in a positive value.
t=232
t=232
The result can be shown in multiple forms.
Exact Form:
t=232
Decimal Form:
t=11.5
Mixed Number Form:
t=1112
Solve for t -3(t-5)+7t=6t-8

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top